PENEGAKAN HUKUM DI ZONA EKONOMI EKSKLUSIF BERDASARKAN KONVENSI PBB TAHUN 1982 TENTANG HUKUM LAUT DAN UNDANG-UNDANG NOMOR 5 TAHUN 1983 TENTANG ZONA EKONOMI EKSKLUSIF INDONESIA - simanjuntak, mangisi (Fakultas Hukum Universitas Kristen Indonesia, 2025)
Law enforcement in Indonesia's Exclusive Economic Zone (EEZ) is carried out in order to secure and exercise sovereign rights to explore and exploit, manage and conserve biological and non-biological natural resources from the seabed and the land below and the water above it and other activities for the economic exploitation of the zone, such as power generation from water, currents and wind. Jurisdiction relating to the manufacture and use of artificial islands, installations and other buildings. Scientific research on marine affairs and the protection and preservation of the marine environment. Law enforcement in Indonesia's EEZ is often constrained by the lack of patrol vessels not proportional to the extent of Indonesia's EEZ. Compared with other ASEAN countries, Indonesia's EEZ area is ranked first, meaning that Indonesia has the largest EEZ, namely 1,577,300 square miles. The extent of Indonesia's EEZ certainly has juridical consequences for securing and enforcing the law (law enforcement).